PERKEMBANGAN SEMANTIK: SEBAB-SEBAB PERUBAHAN MAKNA: PERKEMBANGAN SEMANTIK: SEBAB-SEBAB PERUBAHAN MAKNA - Masyfufah, Siti; April Lia, Hesti Suci; Hidayat, Nandang Sarip (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
This article aims to discuss the study of meaning, changes in meaning, and factors that influence changes in meaning. In addition, it also discusses the impact of changes in meaning, which sometimes lead to new concepts, beliefs, principles, or models that are used as guidelines for language communities. The research method used is qualitative research, through the explanation of data in words or phrases. The research focuses on a conceptual approach to changes in meaning in the semantic aspect of lexicology. The results show that the forms and processes of change in meaning depend on their use in speech or written sentences, including addition, subtraction, or total change, whether in terms of the quantity or quality of words. Changes in meaning in the Arabic language are the result of several factors, namely needs, social and cultural developments, emotions and emotional states, linguistic deviations, changes in meaning from literal to figurative meanings, and innovation or creativity. The factors of change in meaning are: linguistic factors, historical factors, social and cultural factors, scientific and technological progress, the need for new meanings, factors related to speakers of the language, and the influence of foreign languages. يهدف هذا المقال إلى مناقشة دراسة المعنى والتغيرات التي تطرأ عليه والعوامل التي تؤثر على تغير المعنى. بالإضافة إلى ذلك، يناقش أيضًا تأثير التغيرات التي تطرأ على المعنى والتي تؤدي أحيانًا إلى مفاهيم أو معتقدات أو مبادئ أو نماذج جديدة تستخدم كمبادئ توجيهية للمجتمعات الناطقة باللغة. إن أسلوب البحث المستخدم هو البحث النوعي، أي من خلال شرح البيانات الموجودة بالكلمات أو العبارات وليس بالأرقام. ويستخدم محور البحث منهجًا مفاهيميًا حول التغيرات في المعنى في الجانب الدلالي من علم المعجم. وتظهر النتائج أن أشكال التغير في المعنى وإجراءاته تعتمد على استعمالها في اللفظ أو الجملة المكتوبة، ويشمل ذلك التغيير الإضافة أو الطرح أو التغيير الكلي، سواء من حيث كمية الكلمات أو نوعيتها. والتغير في المعنى في اللغة العربية ناتج عن عدة أمور، وهي الحاجات، والتطورات الاجتماعية والثقافية، والمشاعر والنفوس الانفعالية، والانحرافات اللغوية، وتغير المعنى من الألفاظ الجوهرية إلى المعاني المجازية، والابتكار أو الإبداع. وعوامل تغير المعنى هي: عوامل اللغة، والعوامل التاريخية، والعوامل الاجتماعية والثقافية، وعوامل التقدم العلمي والتكنولوجي، والحاجة إلى معانٍ جديدة، وعوامل المتكلمين باللغة، وتأثير اللغات الأجنبية.